ANALISIS PERSEPSI YANG MEMPENGARUHI KEPUTUSAN PEMBELI DI CENTRO PARAGON SOLO - Maria Retno Budi Astuti; Supriyono . (BHIRAWA, 2015)
This study aims are to analysis the influence of perceptions Affecting Buyer Decision In Centro Paragon Solo. Data collection techniques by questionnaire. Test conducted research instrument that covers the validity and reliability as well as the classical assumption of research instruments. Methods of analysis using multiple linear regression , t-test, F and R2. The result of the research hypothesis states that (1) According to the calculation results obtained t value 2,174> of t table 1.985 and 0.032 significance value of t table 1.985 and 0.002 significance value of t table 1.985 and 0.000 significance value 1.985 and the value of t table significance 0.024> 0.05, then Ho is rejected and shopping convenience variable positive and significant impact on purchasing decisions in Centro Paragon Solo. According to the calculations, the t value 5.531> of ttable 1.985 and 0.000 significance value F-tabel value of 2.30 and a significance value of 0.000 < 0.05, then Ho is rejected, there is a significant effect of the variable price, store image, product quality, convenience shopping and completeness of product on purchasing decisions in Centro Paragon Solo, simultaneously. (3) Based on the calculation of Adjusted R2 Square value of 0.931. From the results of these calculations can be concluded that the model used independent variables gives a contribution of 93.1 % on the dependent variable, while the remaining 6.9 % is influenced by other factors outside of the variables studied, eg quality of service, promotions and so on other. Keywords : consumer perceptions , purchasing decisions